Ovary does harbor stem cells - size of the cells matter! - Deepa Bhartiya; Diksha Sharma (BMC, 2020)
Abstract A recent study published in the journal Nature Communications from Karolinska Institute, Sweden was unable to detect stem cells in adult human ovarian cortex by single-cell RNAseq and by studying cell surface antigen profiles by flow cytometry studies. Their findings are startling since stem cells have been well characterized in the adult mammalian ovary of several species including mouse, rabbit, monkey, sheep, pig and humans. Ovarian stem cells include pluripotent, very small embryonic-like stem cells (VSELs) and slightly bigger ovarian stem cells (OSCs) which are easily visualized in smears obtained by gently scraping the ovary surface. The potential of ovarian stem cells to differentiate into oocyte-like structures in vitro and also resulting in the birth of mouse pups has been reported. A possible role of ovarian VSELs in initiation of ovarian cancers has also been delineated. The ovarian stem cells can also be collected by enzymatic digestion of ovarian tissue for various studies, taking care to always pellet the cells suspension at 1000 g since this high speed is required to collect the small-sized stem cell populations (VSELs & OSCs) with high nucleo-cytoplasmic ratio. These stem cells invariably get discarded when cells suspension is spun at lower speed. The cells were spun at 300 g for various experiments in the Karolinska study and this is the underlying reason for their negative results. Stem cells were inadvertently and unknowingly discarded and never got analyzed by single-cell RNAseq and flow cytometry experiments. To conclude, stem cells surely exist in adult mammalian ovary and their role during neo-oogenesis and primordial follicle assembly under physiological conditions is currently being investigated.